(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The current research highlighted the field of judicial accounting as a new area of ​​accounting, which was concerned by fraud cases in the business environment and clarifying the role of judicial accounting in activating the objectives of corporate governance while highlighting the role of corporate governance in achieving the quality of accounting information over five years (From 2005 to 2010). The researcher adopted the descriptive analytical method by tracking and investigating the research material and analyzing it and extracting the results in addition to the study of the content through studying some references and sources related to judicial accounting and its impact on corporate governance and reviewing some studies and financial lists in the National Company for Chemical and Plastic Industries in Iraq to learn about the reality of judicial accounting And the impact on governance. The results of the research result in a relationship between the stakeholders and the competitiveness of the institution. The sample of the study. The internal audit function in the institution has the sample of the study independently in the performance of its tasks. The researcher has the financial and financial resources necessary to perform his duties. And current and prospective clients for adoption on the basis of consistent accounting and legal rules, and that the work of the internal auditor is subject to independent external evaluation.